2010
DOI: 10.1152/ajpgi.00165.2010
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous or luminal amino acids are insufficient to maintain pancreatic growth and digestive enzyme expression in the absence of intact dietary protein

Abstract: We previously reported that rats receiving total parenteral nutrition (TPN) undergo significant pancreatic atrophy characterized by reduced total protein and digestive enzyme expression due to a lack of intestinal stimulation by nutrients (Baumler MD, Nelson DW, Ney DM, Groblewski GE. Am J Physiol Gastrointest Liver Physiol 292: G857-G866, 2007). Essentially identical results were recently reported in mice fed protein-free diets (Crozier SJ, D'Alecy LG, Ernst SA, Ginsburg LE, Williams JA. Gastroenterology 137:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In addition to the lower relative liver mass in PD mice, relative pancreas mass was also reduced by protein deficiency, consistent with the well-established sensitivity of the exocrine pancreas to dietary components including protein (Brannon, 1990; Baumler et al 2010). The composite pancreatitis score in all groups was driven predominantly by leucocyte infiltration, which tended to be higher in infected dams, possibly due to infection-associated systemic inflammatory signals.…”
Section: Discussionsupporting
confidence: 78%
“…In addition to the lower relative liver mass in PD mice, relative pancreas mass was also reduced by protein deficiency, consistent with the well-established sensitivity of the exocrine pancreas to dietary components including protein (Brannon, 1990; Baumler et al 2010). The composite pancreatitis score in all groups was driven predominantly by leucocyte infiltration, which tended to be higher in infected dams, possibly due to infection-associated systemic inflammatory signals.…”
Section: Discussionsupporting
confidence: 78%
“…Maintaining Glu secretion during protein restriction. During total parenteral nutrition and protein-deficient diet, the exocrine pancreatic volume and the synthesis of digestive enzymes are diminished (3,18). However, despite the reduction of pancreas volume and protein synthesis, the secretion of free Glu was unchanged in our animals receiving a proteindeficient diet.…”
Section: Discussionmentioning
confidence: 61%
“…Exocrine pancreas deficiency develops as a result of an insufficient amount or quality of protein arriving in the digestive tract, causing changes to the synthesis and secretion of digestive enzymes and a reduction in organ volume (7,18,29,45). Even when adequate caloric content is supplied intravenously (total parenteral nutrition), morphological and functional alterations in the exocrine pancreas and small intestine are observed (3,70). In these patients, further supplementing parenteral diets with glutamine (Gln) has a positive effect partially restoring the normal homeostasis of small intestine and pancreas (2,24,31).…”
Section: Introductionmentioning
confidence: 99%
“…Baumler et al found that rats receiving total parenteral nutrition (TPN) can develop jejunum atrophy due to lack of nutrient irritation in the bowel 14 . In another report, the same group suggested that oral and intravenous administration of an amino acid formulation improved decreased pancreatic function, but had no effects on atrophy of the jejunal mucous membrane in rats given TPN 15 . These reports suggest that, for villous function in the small intestine, explosive irritation by pancreatic enzymes may play an important role, rather than nutrient irritation of amino acids, and this may be the reason why SDOV reflects PEF.…”
Section: Discussionmentioning
confidence: 99%